Full Spectrum of Reported Symptoms of Bilateral Vestibulopathy Needs Further Investigation—A Systematic Review - Lucieer, Florence; Duijn, Stijn; Van Rompaey, Vincent; Pérez Fornos, Angelica; Guinand, Nils; Guyot, Jean Philippe; Kingma, Herman; van de Berg, Raymond (Frontiers in Neurology, 2018)
OBJECTIVE: To systematically review the symptoms reported by patients with bilateral vestibulopathy (BV) in clinical studies and case reports. This would serve as the first step in establishing a validated patient reported outcome measures for BV. METHODS: A search on symptoms reported by patients with BV was performed in PubMed, and all publications covering these symptoms were included. Exclusion criteria comprised reviews and insufficient details about the frequency of occurrence of symptoms. RESULTS: Fourteen-hundred-forty-two (1442) articles were retrieved. Eighty-eight studies were included (41 clinical studies, 47 case-reports). In consensus, 68 descriptions of symptoms were classified into six common and generic symptoms. Frequency of symptoms in clinical studies and case reports were reviewed respectively; imbalance (91% and 86%), chronic dizziness (58% and 62%), oscillopsia (50% and 70%) and recurrent vertigo (33% and 67%). BV could be accompanied by hearing loss (33% and 43%) and tinnitus (15% and 36%). Fifteen clinical studies and ten case reports reported symptoms beyond vestibular and hearing deficits such as limited social activities, depression, concentration and memory impairment, and reduced quality of life in general. CONCLUSIONS: The literature on BV symptomatology mainly focuses on classic symptoms such as imbalance and oscillopsia, while only few report additional symptoms such as cognitive memory impairment and performing dual tasks. In fact, none of the reviewed clinical studies and case reports provided a comprehensive overview of BV symptoms. In order to develop a validated patient reported outcome measures, qualitative research using semi-structured and unstructured interviews is needed to explore the full spectrum of BV symptoms.